Structural And Geographical Analyses of Polish Labour Market in The Perspective of Professional Activity - Magdalena BRUDZ; Maciej JEWCZAK (Communications of International Proceedings, 2022)
The aim of the paper is to assess and compare Polish NUTS-2 units in terms of professional activity based on the rates of changes in the level of the economically active and inactive number of people, taking into consideration the age division for aged 15 and more in Polish voivodeships in the years 1999-2020. The research assumed incorporating the Berzeg’s panel Shift Share model. Following the multivariate regression results it was possible to verify the statistical significance of estimated global (national), structural and geographical components, along with the assessment of the structural component consistency and tendencies over time.
Keywords: labour market; regional differentiation; structural and geographic analysis; Berzeg’s Panel Shift Share